2020
DOI: 10.2478/jvetres-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

Field trial of primary and booster dose of inactivated vaccine against bovine respiratory bacteria in young Holstein calves

Abstract: AbstractIntroductionThe objective of this research was to evaluate the antibody response to multiple doses of an inactivated mixed vaccine against Histophilus somni, Pasteurella multocida, and Mannheimia haemolytica, and to investigate the influence of age at time of vaccination in the field. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 19 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…Following the grant of the owner’s informed consent, all calves received 1 mL of a primary intramuscular immunisation between the ages of 1 and 3 weeks and a booster immunisation three weeks later. We have previously reported that little difference in antibody titres was observed following the initial immunisation at 1, 2 or 3 weeks of life and the booster ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the grant of the owner’s informed consent, all calves received 1 mL of a primary intramuscular immunisation between the ages of 1 and 3 weeks and a booster immunisation three weeks later. We have previously reported that little difference in antibody titres was observed following the initial immunisation at 1, 2 or 3 weeks of life and the booster ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, our previous study suggested that after the administration of an initial and booster immunisation with a vaccine containing inactivated antigens of Histophilus somni, Pasteurella multocida and Mannheimia haemolytica, the titres of young calves with high maternal antibody levels (MAL) were not lower than those of calves with low MAL. In addition, the percentage of calves that became seropositive was higher in the group with high MAL than in the group with low MAL (15). Whether maternal antibodies inhibit the effectiveness of inactivated vaccines is still unclear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The degree of oxidative stress was expressed as the oxidative stress index (OSI) calculated with the formula (d-ROMs/BAP) × 100 = OSI (1,21). Serum antibody titres against H. somni were detected in ELISA, as described in a previous study (3,14). H. somni of the M-1 Br strain was dispensed into wells of a microtitre plate, and serum samples at 400-fold dilution were added to the wells and incubated, at 30℃ for 1 h. After washing, peroxidase-conjugated anti-bovine IgG was added and the samples were incubated again, at 30℃ for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, inactivated vaccines prime the humoral immune response but are poor at inducing cell-mediated immunity [130]. Additionally, inactivated vaccines require a booster dose in order to achieve protection [131]. Evidence from multiple studies suggests that MLV vaccines are more effective in preventing BRDC than their inactivated vaccine equivalents [125].…”
Section: Current Vaccinesmentioning
confidence: 99%